Animasi “Keluarga Aman” Sebagai Media Sosialisasi Pencegahan Penularan COVID-19 - Suliswaningsih Suliswaningsih; Achmad Masruri; Ganang Eko Saputro; Anugerah Bagus Wijaya; Chyntia Raras Ajeng Widiawati (P3M Politeknik Negeri Cilacap, 2023)
Adaptation to new habits (new normal) must be implemented considering that people must continue their activities amidst the outbreak of Covid-19 transmission cases. Apart from the government and community organizations, awareness of prevention must be carried out by each individual even though they have been vaccinated. The purpose of this research is to create a 2D animation to socialize the application of the 5M health protocol used to prevent widespread transmission of Covid-19. The process of creating a 2D animation titled